Certain risk factors for patients with desmoid tumors warrant reconsideration of local therapy strategies. Issue 14 (28th April 2020) - Bishop, Andrew J.; Landry, Jace P.; Roland, Christina L.; Ratan, Ravin; Feig, Barry W.; Moon, Bryan S.; Zarzour, Maria A.; Wang, Wei‐Lien; Lazar, Alexander J.; Lewis, Valerae O.; Torres, Keila E.; Guadagnolo, B. Ashleigh
Abstract : Background: The objective of this study was to evaluate treatment outcomes for patients with desmoid tumors (DTs) receiving local therapy with surgery alone, radiation therapy (RT) alone, or combined modality therapy (RT and surgery). Methods: This was a cross‐sectional cohort study of 412 patients with nonmesenteric DTs who received local therapy at the authors' institution between 1965 and 2018. Results: The median follow‐up time was 95 months (range, 1‐509 months). Local recurrence occurred in 127 patients (31%) at a median time of 21 months (interquartile range, 12‐38 months). The 5‐year local control (LC) rate was 67%. Patient or tumor factors that were significantly associated with poorer 5‐year LC in a multivariable analysis included an age ≤ 30 years (57% vs 75% for an age > 30 years; hazard ratio [HR], 1.73; P  = .004), an extremity location (57% vs 71% for a nonextremity location; HR, 1.77; P  = .004), and large tumors (59% for >10 cm [HR, 2.17; P  = .004] and 65% for 5.1‐10 cm [HR, 1.71; P  = .02] vs 76% for ≤5 cm). Subset analyses of these high‐risk patients revealed no local therapy strategy to be superior for young patients ≤ 30 years old (HR for surgery, 1.42; P  = .33; HR for RT, 1.36; P  = .38) or for large tumors > 10 cm (HR for surgery, 1.55; P  = .46; HR for RT, 0.91; P  = .91). However, for patients with extremity tumors, surgery alone was significantly associated with inferior LC (HR for surgery, 5.15; P  < .001; HR for RT, 1.51; P  = .38). Conclusions: Local therapy provides durable tumor control in the majority of patients with DTs. However, young patients, patients with an extremity location, and patients with large tumors are at increased risk of recurrence. When active treatment is indicated, systemic therapy should perhaps be considered as a first‐line option in these high‐risk subsets. Prospective multi‐institutional studies evaluating this strategy are warranted. Abstract : Patients with desmoid tumors who are young or have tumors that are large or in the extremities have an increased risk of relapse after local therapy. Therefore, when treatment is indicated in these higher risk subsets, systemic therapies should likely be considered as the first‐line therapy.